(untitled) (Ustozlar uchun, 2026)
This thesis examines the effectiveness of Communicative Language Teaching (CLT) in English as a Foreign Language (EFL) programs through a review of empirical studies from 2015 to 2025. The findings show that CLT significantly enhances learners’ speaking proficiency and overall communicative competence compared to traditional grammar-focused methods. Effective implementation of CLT relies on activity-based learning such as role-plays, problem-solving tasks, and collaborative activities, as well as sufficient teacher training. Although challenges exist in some EFL contexts, evidence consistently supports CLT’s ability to improve real-world communication skills.